Catalytic potential of selected metal ions for bioleaching, and potential techno-economic and environmental issues: A critical review. (April 2017) - Pathak, Ashish; Morrison, Liam; Healy, Mark Gerard
Graphical abstract: Highlights: Use of selected metal ions for promoting the bioleaching efficiency is summarized. The reaction mechanisms of each metal ion is described. Key techno-economic and environmental challenges are discussed. Future prospects for metal ion catalyzed bioleaching processes are discussed. Abstract: Bioleaching is considered to be a low-cost, eco-friendly technique for leaching valuable metals from a variety of matrixes. However, the inherent slow dissolution kinetics and low metal leaching yields have restricted its wider commercial applicability. Recent advancements in bio-hydrometallurgy have suggested that these critical issues can be successfully alleviated through the addition of a catalyst. The catalyzing properties of a variety of metals ions (Ag +, Hg ++, Bi +++, Cu ++, Co ++ etc.) during bioleaching have been successfully demonstrated. In this article, the role and mechanisms of these metal species in catalyzing bioleaching from different minerals (chalcopyrite, complex sulfides, etc.) and waste materials (spent batteries) are reviewed, techno-economic and environmental challenges associated with the use of metals ions as catalysts are identified, and future prospectives are discussed. Based on the analysis, it is suggested that metal ion-catalyzed bioleaching will play a key role in the development of future industrial bio-hydrometallurgical processes.